Performance of flower crops as intercrops in coconut garden in southern dry region of Karnataka - M. Prashanth, T.B. Basavaraju,; Maheswarappa, H.P. (Journal of Plantation Crops, 2018)
An experiment was conducted for three years in a 40 year old coconut garden of Tiptur Tall variety planted with a spacing of 10 m x 10 m to identify suitable flower crops for intercropping in coconut gardens of southern dry region of Karnataka. Five flower crops viz., jasmine (Kakada), chrysanthemum, crossandra, China aster and marigold were grown in the inter-row spaces of coconut. The number of leaves on the crown, annual leaf production, number of bunches and buttons and nut yield of coconut were not significantly influenced by the flower crops grown in coconut garden. The leaf nutrient status of coconut was also not significantly influenced by flower crops. The mean yield of flowers was 1045 kg ha-1 in jasmine, 4393 kg ha-1 in chrysanthemum, 1070 kg ha in crossandra, 2158kg ha-1 in China aster and 4874 kg ha in marigold. The cropping system of coconut + chrysanthemum recorded significantly higher net income (` 200558 ha-1-1) followed by coconut + crossandra (` 179483 ha-1), coconut + jasmine (` 166767 ha), coconut + China aster (` 121692 ha` 54250 ha-1-1) and coconut + marigold (` 96350 ha-1-1-1). The monocrop of coconut recorded significantly the lowest net income. The study indicated the suitability and profitability of chrysanthemum, crossandra, jasmine, China aster and marigold as intercrops in coconut garden.